Un análisis empírico de la diferenciación horizontal de los polígonos industriales gallegos - Pablo de Carlos; Trinidad Domínguez; Elisa Alén (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– Over the past decades, there has been in Galicia, in line with what has happened in other territories, a proliferation of industrial estates that have increased the supply of industrial land in this region. These estates are immersed in a competitive struggle to attract the largest possible number of companies. One of the factors that influence their capacity of attraction is the variety of facilities, both infrastructures and services, which make available to its customers. The intention of this paper is to analyze, through multivariate statistical techniques, if the Galician industrial estates have defined horizontal differentiation strategies that enable them to meet the specific needs of the demand, i.e., firms seeking a location for carrying out their productive activities.
Keywords: M19; L10; R32; 330; Industrial estates; Galicia; Horizontal differentiation strategies; Multivariate statistical techniques